Gestión pedagógica en el aula: Clima social escolar, desde la percepción de estudiantes y profesores del séptimo año de educación básica de los centros educativos Elvia Bélgica Jiménez de Gonzales del sector rural y Escuela Municipal Ecológica del sector urbano de la ciudad, cantón y provincia de Loja, 2011-2012 - Gaona Salinas, Neli Francisca (2013)
The current investigation, framed in meeting learning management and social climate, as elements of measure and description of the environment in which learning processes are developed in the rural elementary School Elvia Bélgica Jiménez de González and the other one Urbana elementary School Municipal Ecológica of the city, canton and province of Loja, 2011-2012 "applied to a sample of 40 students and 2 teachers. Descriptive methods were used, analytical and synthetic techniques used were: observation, survey and critical reading. Instruments were applied as school climate surveys Moos and Trickett CES aimed at teachers and students, the self-assessment questionnaire for learning management and teacher observation sheet the researcher. By knowing about learning management and classroom social climate in schools investigated are detected some weaknesses in these areas, which is why it poses a proposal to strengthen them for the improvement of the educational quality of the institution. As such, we invite you to review this document so that they can provide valuable input.